NEWS FRAMEWORK OF THE ARREST OF DJOKO TJANDRA IN KOMPAS.COM AND DETIK.COM - Bella Febriyana Ananda; Razanah Mutiara Rysan; Fikry Zahria Emeraldien; Juwito Juwito (JOSAR (Journal of Students Academic Research), 2021)
Like conventional media, online media is also active to take part in reporting every reality that is happening around. Online media can influence the meaning and image that results from the reality it constructs. This study aims to identify the news about Djoko Tjandra's arrest in online media Kompas.com and Detik.com. This study uses a qualitative approach with a Robert N. Entman framing analysis method which is carried out with four tools, namely: (1) defining the problem, (2) diagnosing the cause, (3) making moral judgements, (4) treatment recommendations. Object of this research is the news about the arrest of suspect in the corruption case, Djoko Tjandra, by Bareskrim Polri which were uploaded by the two media from 31 July to 7 August 2020. From the research results, Kompas.com uses a frame in the legal field and tends to highlight this case as a legal problem. This is reinforced by the inclusion of legal references, selection of sources with legal backgrounds, and explanations of legal procedures in this case. Meanwhile, Detik.com defines the problem as a violation of the law and presents news related to moral issues such as Djoko Tjandra asking for protection from various parties.